The Correlation between Marketing Mix and Customer Satisfaction in the General Poly Unit at Bhayangkara Hospital, Kupang - Arifin Udju; Petrus Romeo; Yoseph Kenjam (Lontar : Journal of Community Health, 2021)
Patient satisfaction is one of the important things in reviewing the quality of service of a health agency. The marketing mix is ​​a set of tools that play an important role as a company strategy and policy to achieve customer satisfaction. Bhayangkara Hospital is a type C hospital that provides individual health services with inpatient and outpatient treatment, and emergency services. The purpose of this study was to determine the relationship between marketing mix and customer satisfaction in the general poly unit of Bhayangkara Hospital. The research design was an analytic survey with a cross sectional design. The research sample consisted of 90 respondents who were selected using accidental sampling technique. The results of the study found that there was a relationship between product mix (p = 0.003), place (p = 0.037), promotion (p = 0.037), people (p = 0.046), process (p = 0.050) and physical evidence (p = 0.037) with customer satisfaction. And there is no relationship between price mix (p = 0.228) with customer satisfaction. The hospital should pay more attention to the supporting facilities and infrastructure to increase patient comfort in the general poly unit of Bhayangkara Hospital.